(untitled) (E Global Congress, 2025)
The modernization and simplification of the banking system plays an important role in the development of the country’s financial services. Today, information technologies, as in all sectors, are widely implemented in the banking system. It is worth noting that the development of digital banking in the banking system is one of the key issues for economic growth.